Optimization of Titanium Recovery from Tin Tailings Using Flotation Route - Subandrio Subandrio; Wiwik Dahani; Rita Sundari; Riskaviana Kurniawati; Irfan Marwanza; Franko Sajow Darren (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2024)
Titanium has found widespread application across various industries due to its high corrosion resistance. It is commonly used in dental equipment, surgical instruments, bone implants, and marine components, and serves as an engine material in high-temperature environments. Because of its lighter weight compared to steel, titanium has also replaced stainless steel in many construction materials. In Bangka Island, Indonesia, tin tailings have been identified as a potential source of titanium, making the analysis of titanium in these tailings highly significant. This study employed the froth flotation method, known for its simplicity, speed, and cost-effectiveness, to analyze titanium content from tin tailings. Sodium oleate was used as the frother and collector, while sodium chlorate acted as the depressant. The mass ratios of depressant to collector were varied at fixed collector amounts (1:10, 5:10, 10:10, and 15:10) and fixed depressant amounts (10:3, 10:6, 10:9, and 10:12). The highest titanium concentration (2.03%) was achieved with a mass ratio of 10:12, while the optimal titanium recovery (45.51%) in the concentrate occurred with equal amounts (3.75 g) of depressant and collector, or at a mass ratio of 10:10, at 15 minutes of flotation time and neutral pH. X-ray fluorescence (XRF) and X-ray diffraction (XRD) analyses indicated that the tin tailings primarily contained silicate and zircon minerals, with traces of titanium in the form of rutile, ilmenite, and titanate. These findings contribute valuable insights for future titanium extraction and processing industries.